DISTINCT TEMPORALITIES IN THE BREAST CANCER DISEASE PROCESS - Janderléia Valéria Dolina; Roseney Bellato; Laura Filomena Santos de Araújo (SciELO, 2014)
Comprehensive approach study aimed understanding the reflections and contrasts between personal time and medical therapy protocol time in the life of a young woman with breast cancer. Addressed as a situational study and grounded in Beth's life story about getting sick and dying of cancer at age 34, the study's data collection process employed interviews, observation and medical record analysis. The construction of the analytic-synthetic box based on the chronology of Beth's clinical progression, treatment phases and temporal perception of occurrences enabled us to point out a linear medical therapy protocol time identified by the diagnosis and treatment sequencing process. On the other hand, Beth's experienced time was marked by simultaneous and non-linear events that generated suffering resulting from the disease. Such comprehension highlights the need for healthcare professionals to take into account the time experienced by the patient, thus providing an indispensable cancer therapeutic protocol with a personal character.